Integrating the Triple Bottom Line into the Vehicle Routing Problem: a transdisciplinary approach to customer prioritization - Trigos, Federico; Osorio, María Lucila (Frontiers in Sustainability, 2025)
The current business environment is characterized by heightened competition, rising customer expectations, and increasing demands for cost efficiency and sustainability. Within this context, management's mandate for a seamless flow of products to customers, especially those with high priority, is underscored by imperatives to lower costs, adhere to policies and regulations, and sustain personnel wellbeing and motivation. This research advances the Vehicle Routing Problem (VRP) by integrating a transdisciplinary approach to customer prioritization that extends beyond revenue-based metrics. By incorporating customer preferences and sustainability considerations alongside traditional economic and logistical factors into the decision-making process, the model ensures a more efficient allocation of resources and improved customer service, ultimately enhancing long-term profitability. A real-world numerical illustration is provided, demonstrating that order acceptance is crucial and highlighting that not all customers should be served when considering the Triple Bottom Line (TBL) objectives. The study further explores how prioritization strategies, when managed across different business functions, can lead to better alignment with TBL, balancing economic, social, and environmental goals. The model's application offers significant practical implications for businesses operating under resource constraints, helping them optimize routes, reduce operational costs, and achieve sustainable growth while maintaining high customer satisfaction. Finally, the paper presents avenues for future research, including expanding the model's scope to incorporate reverse logistics and further refining customer prioritization strategies.